Heterogeneity of immune cells in human atherosclerosis revealed by scRNA-Seq - Vallejo, Jenifer; Cochain, Clement; Zernecke, Alma; Ley, Klaus (Cardiovascular Research, 2021)
Immune cells in atherosclerosis include T, B, natural killer (NK) and NKT cells, macrophages, monocytes, dendritic cells (DCs), neutrophils, and mast cells. Advances in single-cell RNA sequencing (sRNA-Seq) have refined our understanding of immune cell subsets. Four recent studies have used scRNA-Seq of immune cells in human atherosclerotic lesions and peripheral blood mononuclear cells (PBMCs), some including cell surface phenotypes revealed by oligonucleotide-tagged antibodies, which confirmed known and identified new immune cell subsets and identified genes significantly up-regulated in PBMCs from HIV+ subjects with atherosclerosis compared to PBMCs from matched HIV+ subjects without atherosclerosis. The ability of scRNA-Seq to identify cell types is greatly augmented by adding cell surface phenotype using antibody sequencing. In this review, we summarize the latest data obtained by scRNA-Seq on plaques and human PBMCs in human subjects with atherosclerosis.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Antibodies; Atherosclerosis; Human; scRNA-Seq; Transcriptomes